Clinical features of patients with invasive thymoma: A retrospective analysis of 61 cases. Issue 4 (18th October 2013) - Imai, Hisao; Kaira, Kyoichi; Yoshino, Reiko; Sato, Koji; Shimizu, Kimihiro; Kawashima, Osamu; Tanaka, Shigebumi; Mori, Masatomo
<x xml:space="preserve">Abstract</x> Aim Invasive thymomas are rare tumours of the anterior mediastinum. These tumours' clinical features have been the subject of much controversy. Therefore, it is necessary to elucidate the optimal management of invasive thymomas. Patients and Methods A total of 61 patients with invasive thymoma were retrospectively reviewed. Results The study group comprised 38 males (62.3 per cent) and 23 females (37.7 per cent), with a median age of 55 years (range: 28–79 years). According to the Masaoka staging, 31 patients had stage II disease (50.8 per cent), 21 patients had stage III disease (34.4 per cent), four patients had stage IVa disease (6.6 per cent) and five patients had stage IVb disease (8.2 per cent). A statistically‐significant difference in the survival rate was observed between stages II and III (P < 0.001) and between III and IV (P < 0.001). Complete resection was performed in 43 patients (70.5 per cent). Patients who underwent complete resection showed significantly better prognosis than those with incomplete resection (P < 0.001) and inoperable/biopsy (P < 0.001). After initial treatment, a total of 20 patients (32.8 per cent) relapsed. The recurrence rates in stages II, III and IV were 3.2 per cent, 66.7 per cent and 55.5 per cent, respectively. Treatment for recurrence was performed in all 20 patients. Conclusion The outcome of invasive thymoma was correlated with the Masaoka stage and the extent of tumour resection. Salvage treatment for recurrent thymoma might give a moderate response rate and improve survival. A large‐scale study is warranted for evaluating the role of the multimodality therapeutic approach in patients with invasive thymoma.